Model of Strengthening Nationalism and Mapping Radical Understanding in Pacitan Islamic Boarding Schools - Mukodi Mukodi (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2022)
The purpose of this study was to describe the vital elan of nationalism in students' souls, explain students' understanding of the dangers of radicalism, analyze the model of strengthening nationalism in Islamic boarding schools, and analyze the mapping model of radicalism in Islamic boarding schools. This research method is a grounded research model with a naturalistic paradigm. Data were collected using in-depth interviews and documentation. Meanwhile, the data analysis used inductive-naturalistic-interpretive techniques. The results of this research found that the expression of the elan vital of nationalism in the soul of the santri is shown through obedience, respect for state symbols, obedience to government rules, and living the substantive meaning of symbols and state philosophy. The form of thought is in the form of the belief that the concept of the Four Pillars of Nationality is final, while the action is in the form of implementing the values of the Four Pillars of Nationality through learning and daily activities.